1994
DOI: 10.1136/gut.35.11.1632
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine inhibits in vivo growth of human colon cancer and reverses histamine stimulated in vitro and in vivo growth.

Abstract: The effect of histamine and cimetidine on the growth of four human colon cancer cell lines was studied. Histamine significantly stimulated the uptake of tritiated thymidine in vitro in a dose dependent manner, to a maximum of 120% and 116% of controls for C170 and LIM2412, respectively. This effect was antagonised by cimetidine, but not diphenhydramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 18 publications
3
73
0
1
Order By: Relevance
“…The presence of a large number of mast cells, which produce histamine, in colorectal cancer tissue was shown to be associated with a worsened prognosis in patients (26). Adams et al reported that histamine stimulated the proliferation of human colorectal tumor cell lines, which was inhibited by cimetidine treatment, though cimetidine did not affect the basal proliferating ability of these cell lines in the absence of histamine (27). Previously, we used a 3 H-methyl-thymidine incorporation assay with human HCC cell lines (HepG2 and KYN-2 cimetidine tended to inhibit cell growth stimulated by histamine, but did not have an effect on the basal proliferating ability of the cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a large number of mast cells, which produce histamine, in colorectal cancer tissue was shown to be associated with a worsened prognosis in patients (26). Adams et al reported that histamine stimulated the proliferation of human colorectal tumor cell lines, which was inhibited by cimetidine treatment, though cimetidine did not affect the basal proliferating ability of these cell lines in the absence of histamine (27). Previously, we used a 3 H-methyl-thymidine incorporation assay with human HCC cell lines (HepG2 and KYN-2 cimetidine tended to inhibit cell growth stimulated by histamine, but did not have an effect on the basal proliferating ability of the cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that histamine was a growth factor for certain cancers and could, by itself, stimulate tumor cell proliferation [18][19][20] . As one of the many important chemo-mediators involved in immune responses, histamine had inhibitory effects on immune response [35][36][37][38] via its H 2 receptors [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Administration of CIM has been found to preserve, to some degree, the patients' perioperative immunity [5,6] , to improve the survival of patients with colorectal cancer, melanoma, and renal cell cancer [7][8][9][10][11][12][13][14][15] . Although it is not clear whether this effect of CIM on cancer is direct or indirect, it has been proposed that CIM may act by enhancing the host immune response to tumor cells [16,17] or by blocking the cell growth-promoting activity of histamine in cancer cell lines [14,[16][17][18][19][20] . In this study, we used CIM in the perioperative period as an adjuvant immunomodulatory agent, and studied its effects on peripheral blood lymphocytes, NK cells and TIL in a randomized controlled clinical trial in patients with GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of histamine are known to occur in colorectal cancer tissues (Garcia-Caballero et al, 1993). Histamine stimulates the in vivo growth of experimental colorectal tumours and cimetidine can inhibit this effect (Adams et al, 1994a). However, other, far more potent H 2 receptor antagonists such as ranitidine do not show the same effect either in vitro (Lawson et al, 1996), or in large clinical trials (Nielsen et al, 1998).…”
mentioning
confidence: 99%